2011
DOI: 10.11613/bm.2011.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods: Passing and Bablok regression

Abstract: The com pa ri son of met ho ds expe ri me nt is im por ta nt pa rt in pro ce ss of ana lyti cal met ho ds and in stru men ts va li da tion. Pas si ng and Bab lok reg ression ana lysis is a sta tis ti cal pro ce du re that al lows va luab le es ti ma tion of ana lyti cal met ho ds ag ree me nt and pos sib le syste ma tic bias be tween them. It is ro bu st, no n-pa ra met ric, non sen si ti ve to dis tri bu tion of errors and da ta out lie rs. As sum ptio ns for pro per ap pli ca tion of Pas si ng and Bab lok re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
170
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(172 citation statements)
references
References 0 publications
0
170
1
1
Order By: Relevance
“…The results of the Passing and Bablok procedure were supplemented with a Bland–Altman plot. The Bland–Altman plot is a graphical method to compare two measurement techniques 7. The level of significance was accepted as P <0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the Passing and Bablok procedure were supplemented with a Bland–Altman plot. The Bland–Altman plot is a graphical method to compare two measurement techniques 7. The level of significance was accepted as P <0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the other frequently proposed method, the Deming regression ( 4 ), the Passing and Bablok regression could be preferred for comparing clinical methods, because it does not assume measurement error is normally distributed, and is robust against outliers. However, it needs the residuals analysis, the distribution of difference around fitted regression line, for a complete interpretation of regression results ( 5 ). This is quite similar, but more complicated than the analysis of differences, described below.…”
Section: Correlation and Linear Regressionmentioning
confidence: 99%
“…To evaluate the effects of recentrifugation on positive results near the positive cut-off concentration, we focused our analysis only on concentrations lower than the 50th percentile within our study sample of 189 specimens (first determination, <190 ng/L; 94 specimens). Nonparametric Passing-Bablok regression analysis 16,17 showed that after recentrifugation, a median reduction of 10 ng/L (95% confidence interval [CI], -37.5 --10.0 ng/L) in troponin I concentrations was observed ( Figure 1). A difference plot for the paired data appear in Figure 2.…”
Section: Resultsmentioning
confidence: 99%